Distribution, Sources, and Biogeochemistry of Carbon Pools (DIC, DOC, and POC) in the Mangrove-Fringed Zhangjiang Estuary, China - Yan, Ran; Feng, Jianxiang; Wang, Yuming; Fu, Linxi; Luo, Xiangxin; Niu, Lixia; Yang, Qingshu (Frontiers in Marine Science, 2022)
The lateral carbon export related to mangroves is of great scientific significance and ecological value in the global carbon cycle. The dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), particulate organic carbon (POC), and stable isotopes (δ13CPOC) of water samples were quantified in the flood (September 2020) and dry (January 2021) seasons in Zhangjiang Estuary. The results revealed that the carbon compositions in the tidal channel of the Zhangjiang Estuary are as follows: DIC > DOC > POC in both seasons. Except for the POC in the site near the sluice, the contents of all carbon compositions were significantly larger in the flood season than those in the dry season (p< 0.05). In the flood season, the POC and DOC exhibited similar spatial characteristics that all sites from the lower sites to the mouth were significantly larger than the site near the sluice. The DIC had an increasing trend from the upper site to the mouth. In the dry season, DIC and DOC displayed patchy distribution under the influence of mariculture and the sluice, while the POC had a decreasing trend from the upper site to the mouth. The MixSIAR model indicates that the source of the POC is overwhelmingly the mariculture, averagely accounting for 42.7% in the flood season and 52.6% in the dry season, mainly in the form of microalgae. The average contribution of mangrove to POC was 33.1% in the flood season and 39.3% in the dry season. The DIC-δ13CPOC and DOC-POC relationships represent the biogeochemical process of microbial photosynthesis and the physical process of adsorption-desorption of organic carbon by redundancy analysis, respectively. This initial dataset for this region should be included in other studies to improve the mangrove outwelling estimate.